TENDENCIAS Y ASUNTOS ECONÓMICOS ASIATICOS EMERGENTES - Yamazawa, Ippei (1997)
Despite the continued high growth of the economies of East and Southeast Asian countries, referred to as the "East Asian miracle", the growth of these economies slowed down in 1996 compared to the previous two years. In view of this, it is suggested that high growth in the region will return in the medium or long term if five conditions are met: (i) structural changes in Asian production and trade, which will generate high productivity growth; (ii) economic opening policies, which include not only greater access to technology and foreign capital, but also increased competitiveness and efficiency; (iii) joint liberalization efforts, which will contribute to the rapid industrialization of the countries in the region by providing capital, technology and export markets; (iv) stabilization of the monetary system, so that exchange rates adjust flexibly and a stable flow of funds is maintained; and (v) resolution of environmental pollution and unstable and insufficient energy and food supplies, which create bottlenecks and impede continued high growth.